2009
DOI: 10.5194/acp-9-6775-2009
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for ice particles in the tropical stratosphere from in-situ measurements

Abstract: Abstract. In-situ ice crystal size distribution measurements are presented within the tropical troposphere and lower stratosphere. The measurements were performed using a combination of a Forward Scattering Spectrometer Probe (FSSP-100) and a Cloud Imaging Probe (CIP), which were installed on the Russian high altitude research aircraft M55 "Geophysica" during the SCOUT-O 3 campaign in Darwin, Australia. One of the objectives of the campaign was to characterise the Hector convective system, which appears on an … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
113
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 106 publications
(127 citation statements)
references
References 63 publications
9
113
2
Order By: Relevance
“…De Reus et al (2009) reported cirrus measurements showing a peak in the ice crystal number size distribution at about 10 µm diameter, while Lawson et al (2008) reported subvisible cirrus observations from Costa Rica with average values of ice particle number concentration (0.066 cm −3 ), and effective radius (8.82 µm) similar to those by McFarquhar et al (2004).…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…De Reus et al (2009) reported cirrus measurements showing a peak in the ice crystal number size distribution at about 10 µm diameter, while Lawson et al (2008) reported subvisible cirrus observations from Costa Rica with average values of ice particle number concentration (0.066 cm −3 ), and effective radius (8.82 µm) similar to those by McFarquhar et al (2004).…”
Section: Introductionmentioning
confidence: 52%
“…De Reus et al (2009) found such effect more marked with increasing IWC, and r eff , i.e. given the general trends of these two quantities with altitude, for thick, low cirrus clouds (Heymsfield and McFarquhar, 2002).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Substantial mixing ratios of several hundred ppt inorganic chlorine have been observed in the marine boundary layer (Pszenny et al, 1993), but the supposition of rapid transport to the TTL seems unwarranted because of loss by wet deposition (e.g. Crutzen and Lawrence, 2000;Mari et al, 2000). A contribution of chlorine from sea salt aerosol Fig.…”
Section: Individual Case Study Simulationsmentioning
confidence: 99%
“…Deep convective clouds may even overshoot into the stratosphere, injecting trace gases, water vapour, and even ice crystals directly (Corti et al, 2008;de Reus et al, 2009). There has been an ongoing debate about whether these injections lead to dehydration or hydration of the stratospheric air.…”
Section: Introductionmentioning
confidence: 99%